Regulating beneficial ownership practices in Malaysia - Kamaruddin, Nursyakila; Tahir, Nor Suziwana; Othman, Sarina; Kamaruddin, Saslina (Faculty of Administrative Science and Policy Studies, 2025)
Money laundering is the process of acquiring money illegally and trying to hide the illegal activity by converting the money into legitimate money through the use of financial and non-financial institutions. Most of the country's efforts are to fight against criminal activity. The recent trend in money laundering is to have multiple layers of beneficial ownership in the company through the concealment of beneficial owners in corporate vehicles. Beneficial ownership has gained significant attention , as governments and regulatory bodies worldwide have attempted to address issues related to money laundering, tax fraud, and the use of complex corporate structures to hide the real owners of assets. In response to international standards of money laundering and terrorism financing set by the Financial Action Task Force (FATF). Malaysia has introduced legal and policy measures which aim to enhance the transparency and accountability in corporate structure. Most countries have a system for obtaining information on the legal person or owner of the company. This paper will examine the current regulatory framework governing beneficial ownership in Malaysia, which includes the requirements under the International Standard of the Financial Action Task Force (FATF), Bank Negara Malaysia (BNM), and Companies Commission of Malaysia (SSM). It will also highlight the vulnerabilities of ultimate beneficial ownership (UBO) and challenges in implementing it in Malaysia.